2014
DOI: 10.1080/13803395.2014.903899
|View full text |Cite
|
Sign up to set email alerts
|

“Good-old-days” bias: A prospective follow-up study to examine the preinjury supernormal status in patients with mild traumatic brain injury

Abstract: This study thus might be the first one to prospectively reveal the progression of the "good-old-days" bias in patients with mTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…These Cohen d effect sizes, although limited by distribution skewing, are within the range of prior studies, which found small (0.23) to large (0.78) GB effects. [10][11][12]16,18 In summary, we found weak support for hypothesis 1.…”
Section: Resultscontrasting
confidence: 44%
See 4 more Smart Citations
“…These Cohen d effect sizes, although limited by distribution skewing, are within the range of prior studies, which found small (0.23) to large (0.78) GB effects. [10][11][12]16,18 In summary, we found weak support for hypothesis 1.…”
Section: Resultscontrasting
confidence: 44%
“…16,18,24 Preinjury symptom reporting was moderately stable over time in our study. A similar number of participants in our full sample reported increased versus decreased preinjury symptoms from 6 weeks to 1 year postinjury.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations